Ecological circular agriculture: A case study evaluating biogas slurry applied to rice in two soils. (August 2022) - Wang, Qingqing; Huang, Qing; Wang, Jiaxin; Li, Huashou; Qin, Junhao; Li, Xiaohui; Gouda, Shaban G.; Liu, Yin; Liu, Quan; Guo, Genmao; Khan, Muhammad Amjad; Su, Xuesong; et al.
Abstract: In the context of carbon peak, neutrality, and circular agricultural economy, the use of renewable resources from agricultural processing for plant cultivation still needs to be explored to clarify material flow and its ecological effects. Paddy-upland rotation is an effective agricultural strategy to improve soil quality. This study evaluated the effects of biogas slurry application against those of chemical fertilisers in these two typical Chinese cropping soils. The application of biogas slurry increased total carbon content in paddy soil by 73.4%, and that in upland soil by 65.8%. Conversely, application of chemical fertiliser reduced total carbon in both soil types. There were significant positive correlations between total carbon and Zn, Cu, and Pb in rice husks grown in paddy soil (R 2  = 0.95, 0.996, 0.95; p  < 0.05). The content of amylose in biogas slurry treatment of paddy soil increased by 35.9%, while that in upland soil decreased by 19.2%. After biogas slurry was applied, the contents of fulvic acid- and humic acid-like substances in paddy soil average increased by 40.9% and 45.6%, while the contents of protein-like components were enhanced by 46.8% in upland soil. This result was consistent with predictions of microbial community function. Microorganisms in paddy soil generally preferred carbon fixation, while those in upland soil preferred hydrocarbon degradation and chemoheterotrophy. Understanding the changes in soil carbon stock and microbial function after biogas slurry application will contribute to sustainable agricultural development and food security. Graphical abstract: Image 1 Highlights: Carbon storage increase was similar in paddy and upland soils at 20% slurry rate. Dominant components of dissolved organic matter differed between the two soil types. Macronutrients accumulated in the grain produced by rice in upland soil. Rice quality was enhanced in slurry treatments of upland soil compared to control. Soil microbial community improved with slurry compared to chemical fertilisers.